2010
DOI: 10.1007/s10725-010-9454-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of phytochelatins and antioxidant defence system in Brassica juncea and Vigna radiata in response to chromium treatments

Abstract: Growth performance, chromium (Cr) accumulation potential and induction of antioxidative defence system and phytochelatins (PCs) were studied in hydroponically grown Brassica juncea (Indian mustard) and Vigna radiata (mungbean) at various levels of Cr treatments (0, 50, 100, 200 lM Cr). B. juncea accumulated twofolds and threefolds higher Cr in root and shoot, respectively than in V. radiata. Compared to B. juncea, V. radiata was found to be particularly sensitive to Cr as observed by the severity and developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 74 publications
(79 reference statements)
3
46
0
1
Order By: Relevance
“…Wani et al (2012), also reported that the root of the various plants including cereals was the first organ that was directly exposed to metal in soil and hence was the target of stressor molecules including heavy metals. Diwan et al (2010) used the root growth as an important parameter in classifying heavy metal tolerance. Therefore, tolerance degrees of the cultivars in the germination stage were also evaluated by looking at the length root reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Wani et al (2012), also reported that the root of the various plants including cereals was the first organ that was directly exposed to metal in soil and hence was the target of stressor molecules including heavy metals. Diwan et al (2010) used the root growth as an important parameter in classifying heavy metal tolerance. Therefore, tolerance degrees of the cultivars in the germination stage were also evaluated by looking at the length root reduction.…”
Section: Resultsmentioning
confidence: 99%
“…The root length of Hibiscus esculentus at different chromium treatment 0. A study on stress tolerance suggests that mechanism of tolerance helps plant to maintain growth even in the presence of potentially toxic metal concentrations [43,44] used the root and shoot Open Access AJPS Phytotoxicity of Chromium on Germination, Growth and Biochemical Attributes of Hibiscus esculentus L.…”
Section: Effect Of Chromium On Tolerance Indexmentioning
confidence: 99%
“…Similar responses of inhibitory activity of Cr on root and shoot length was reported in rice . This reduction could be due to the accumulation of high concentration of Cr in roots and/or a nonexistence of any defined Cr translocation mechanism, thereby enhancing the Cr sequestration in the tissue thus, inhibiting root development (Diwan et al, 2010;Lu et al, 2004).…”
Section: Resultsmentioning
confidence: 99%